Motivation to teach and preparedness for teaching among preservice teachers in China: The effect of conscientiousness and constructivist teaching beliefs - Huang, JiaLi; Sang, Guoyuan; He, Wenjie (Frontiers in Psychology, 2023)
Preparedness to teach refers to the degree of confidence preservice teachers have, and reflects their actual ability. The development of preparedness to teach is an important part of preservice teachers’ professionalization. A substantial body of literature has documented the critical influence of motivation to teach on preparedness; however, how this relation is impacted by mediating and moderating mechanisms remains unclear. The present study constructed a mediated moderation model through structural equation modeling and multigroup tests using 383 questionnaires completed by preservice teachers in China. The findings indicate that the preservice teachers’ gender, teaching experience, and level of certainty about their future choice of a teaching career all influence their preparedness to teach. Specifically, preservice teachers who believe that they will choose a teaching career in the future have more intrinsic motivation, constructivist teaching beliefs, and preparedness to teach. Moreover, preservice teachers’ motivation for teaching can positively predict their constructivist teaching beliefs and preparedness to teach, but their constructivist teaching beliefs alone do not have a mediating effect on the relationship between motivation for teaching and preparedness to teach. However, the findings reveal that the constructivist teaching beliefs of preservice teachers with high conscientiousness can have a partial mediating effect on the relation of motivation for teaching to preparedness to teach. Additionally, conscientiousness plays a moderating role in the influence of constructivist teaching beliefs on preparedness to teach. The study provides meaningful insights into the within-personal traits of how and when motivation for teaching affects preparedness to teach, providing suggestions of PSTs’ recruitment, training, and supports to teacher education program for preparing high-quality teachers.